2001
DOI: 10.1046/j.1432-1327.2001.02002.x
|View full text |Cite
|
Sign up to set email alerts
|

Resistance to induced apoptosis in the human neuroblastoma cell line SK‐N‐SH in relation to neuronal differentiation

Abstract: Much evidence suggests that apoptosis plays a crucial role in cell population homeostasis that depends on the expression of various genes implicated in the control of cell life and death. The sensitivity of human neuroblastoma cells SK-N-SH to undergo apoptosis induced by thapsigargin was examined. SK-N-SH were previously differentiated into neuronal cells by treatments with retinoic acid (RA), 4b-phorbol 12-myristate 13-acetate (PMA) which increases protein kinase C (PKC) activity, and staurosporine which dec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

10
49
0

Year Published

2004
2004
2011
2011

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 60 publications
(59 citation statements)
references
References 48 publications
10
49
0
Order By: Relevance
“…Antiapoptotic Bcl-2 is one of the most important members that inhibits the mitochondria-dependent apoptotic pathway triggered by diverse cytotoxic agents through blocking mitochondrial permeability transition. Indeed, the upregulation of Bcl-2 was associated with the drug-resistant phenotype of certain human tumors (Dole et al, 1994;Lombet et al, 2001). Most intriguingly, our expression studies revealed that antiapoptotic Bcl-2 was constitutively overexpressed in LA-N-5 and RTBM1 cells, whereas its expression levels were extremely low in CHP134 and NB-39-nu cells.…”
Section: Discussionmentioning
confidence: 60%
“…Antiapoptotic Bcl-2 is one of the most important members that inhibits the mitochondria-dependent apoptotic pathway triggered by diverse cytotoxic agents through blocking mitochondrial permeability transition. Indeed, the upregulation of Bcl-2 was associated with the drug-resistant phenotype of certain human tumors (Dole et al, 1994;Lombet et al, 2001). Most intriguingly, our expression studies revealed that antiapoptotic Bcl-2 was constitutively overexpressed in LA-N-5 and RTBM1 cells, whereas its expression levels were extremely low in CHP134 and NB-39-nu cells.…”
Section: Discussionmentioning
confidence: 60%
“…In line with these results, a substantial reduction of cell viability was found in an LDH release assay, suggesting that over-expression of CADM1 in human neuroblastoma cell lines does not only reduce proliferation, but might also function as a proapoptotic or pronecrotic regulator. CADM1 over-expression is known to induce apoptosis in A549 non-small cell lung cancer cells (Mao et al, 2004), but many human neuroblastoma cell lines show considerable resistance to apoptosis when exposed to common apoptosis inducing triggers (Teitz et al, 2000;Lombet et al, 2001). Therefore, further experiments are necessary to more precisely delineate the mechanisms by which CADM1 triggers changes in growth properties and loss of cell viability.…”
Section: Discussionmentioning
confidence: 99%
“…17,18 Bax expression is not significantly modified. 15 Therefore, although both MPA and retinoic acid induce similar morphologic differentiation in neuroblastoma cells, the molecular mechanisms involved appear to be different. In conclusion, MPA, at concentrations corresponding to those of the active free drug readily attainable therapeutically using mycophenolate mofetil, induces neuroblastoma cells to differentiate toward the neuronal phenotype, confirming a potential role of CellCept in the management of neuroblastoma patients.…”
Section: Dear Sirmentioning
confidence: 99%